Comparison of strontium isotope ratios in Mexican human hair and tap water as provenance indicators. (September 2020) - Ammer, Saskia T.M.; Kootker, Lisette M.; Bartelink, Eric J.; Anderson, Bruce E.; Cunha, Eugénia; Davies, Gareth R.
Highlights: 87 Sr/ 86 Sr of 101 human hair and 151 tap water samples are reported from across Mexico. 87 Sr/ 86 Sr ratios range between 0.70424 and 0.71613 (ΔSrmax–min  = 0.01189) in Mexican human hair samples. 87 Sr/ 86 Sr ratios range between 0.70404 and 0.71385 (ΔSrmax–min  = 0.00981) in Mexican tap water samples. A strong correlation (R 2  = 0.80) is observed between 87 Sr/ 86 Sr of human hair and tap water data. These data provide the basis for provenance studies in forensic anthropology. Abstract: Deceased undocumented border crossers are some of the most difficult individuals to identify due to the inability to narrow down the region of origin and therefore to obtain family reference samples for DNA comparison. The isotopic compositions of various body tissues have been demonstrated to be useful biomarkers for tracking locations and movements to aid in the identification of human remains. This study closes the large spatial gap of available 87 Sr/ 86 Sr ratios from North America in tap water and presents the first 87 Sr/ 86 Sr human tissue-based ratios from Mexico. The 101 hair samples from 32 locations in Mexico range in 87 Sr/ 86 Sr ratios from 0.70424 to 0.71613 (ΔSrmax–min  = 0.01189). Furthermore, 151 tap water samples from 51 locations range between 0.70404 to 0.71385 (ΔSrmax–min  = 0.00981). Overall, small variations in the hair and tap water samples collected from individual locations were recorded (ΔSrmax–min  = 0.00041 and 0.00034 respectively). Despite the fact that Mexico is one of the largest bottled water consumers in the world, the 87 Sr/ 86 Sr ratios of human hair and tap water correlated strongly (R 2  = 0.87 for location averages and R 2  = 0.80 when using individual data points). These data represent a valuable resource for identifying the provenance of human remains.